2010
DOI: 10.1039/b926849a
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analysis of the frequencies and rates of cytokine secretion from single cells by quantitative microengraving

Abstract: Summary The large diversity of cells that comprise the human immune system requires methods that can resolve the individual contributions of specific subsets to an immunological response. Microengraving is process that uses a dense, elastomeric array of microwells to generate microarrays of proteins secreted from large numbers of individual live cells (~104–105 cells/assay). In this paper, we describe an approach based on this technology to quantify the rates of secretion from single immune cells. Numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
206
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 47 publications
5
206
0
Order By: Relevance
“…After a short incubation (1-2 hours), the glass is removed to yield an array of cytokines registered to the array of microwells. Using this method, we have demonstrated, and confirmed with quantitative models, the ability to measure the secretion of IFN-γ, IL-2, and TNF-α simultaneously from polyclonally activated, primary T cells ex vivo with sensitivities 10- to 100-fold greater than ELISpot and surface-based capture (27).…”
Section: Detection Of Hiv-specific Cytotoxic Effector T Cells From CLmentioning
confidence: 86%
See 1 more Smart Citation
“…After a short incubation (1-2 hours), the glass is removed to yield an array of cytokines registered to the array of microwells. Using this method, we have demonstrated, and confirmed with quantitative models, the ability to measure the secretion of IFN-γ, IL-2, and TNF-α simultaneously from polyclonally activated, primary T cells ex vivo with sensitivities 10- to 100-fold greater than ELISpot and surface-based capture (27).…”
Section: Detection Of Hiv-specific Cytotoxic Effector T Cells From CLmentioning
confidence: 86%
“…In the absence of a direct assay to measure both functions (cytolysis and secretion), it has remained unclear to what extent cells exhibit both responses concurrently when encountering an APC. We have previously shown that the elastomeric array of microwells used here can also detect the frequencies and rates of secretion of multiple cytokines by a process called microengraving (26,27). According to this method, a glass slide coated with antibodies specific for .…”
Section: Detection Of Hiv-specific Cytotoxic Effector T Cells From CLmentioning
confidence: 99%
“…In addition, because the droplets in the above methods are fully sheathed by a carrier fluid, they are designed primarily for studies with suspended cells. There are methods that bypass the production and capturing under flow altogether by initially producing stationary plugs within the geometry of the device (2,(23)(24)(25). However, upon their adjustment to prolonged mammalian assays, they require multilayer fabrication, either involving high-pressure cell loading or not allowing for different substrates to be used (26,27).…”
mentioning
confidence: 99%
“…However, the limited protein detection range and the lack of detection sensitivity of current techniques are obstacles in the monitoring and study of secreted proteins from single cells. 3,4 One of the ways to circumvent such concerns is the use of protein microarrays that are commonly utilized for the high-throughput screening and analysis of protein interactions. [5][6][7] Protein microarrays rely on the capture of secreted proteins from cells on a support surface, for example, a nitrocellulose membrane, glass slide, or microtiter plate, and detection by the fluorescent dye-labeled probe molecules added to the array.…”
Section: Introductionmentioning
confidence: 99%